Predictions for the cosmogenic neutrino flux in light of new data from the Pierre Auger Observatory - Anchordoqui, L; Goldberg, H; Hooper, D; Sarkar, S; Taylor, A (American Physical Society, 2007)
The Pierre Auger Observatory (PAO) has measured the spectrum and composition of the ultrahigh energy cosmic rays with unprecedented precision. We use these measurements to constrain their spectrum and composition as injected from their sources and, in turn, use these results to estimate the spectrum of cosmogenic neutrinos generated in their propagation through intergalactic space. We find that the PAO measurements can be well fit if the injected cosmic rays consist entirely of nuclei with masses in the intermediate (C, N, O) to heavy (Fe, Si) range. A mixture of protons and heavier species is also acceptable but (on the basis of existing hadronic interaction models) injection of pure light nuclei (p, He) results in unacceptable fits to the new elongation rate data. The expected spectrum of cosmogenic neutrinos can vary considerably, depending on the precise spectrum and chemical composition injected from the cosmic ray sources. In the models where heavy nuclei dominate the cosmic ray spectrum and few dissociated protons exceed GZK energies, the cosmogenic neutrino flux can be suppressed by up to two orders of magnitude relative to the all-proton prediction, making its detection beyond the reach of current and planned neutrino telescopes. Other models consistent with the data, however, are proton-dominated with only a small (1-10%) admixture of heavy nuclei and predict an associated cosmogenic flux within the reach of upcoming experiments. Thus a detection or non-detection of cosmogenic neutrinos can assist in discriminating between these possibilities.